Pelatihan Pembuatan Gasnish Minuman dan Tumpeng Bagi Siswa/siswi SMK - Esteria Priyanti; Ira Handayani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Learning in making food and drink garnishes has been integrated into the vocational school curriculum, but there is a problem faced by students when the learning process for making garnishes in class X takes place online due to the Covid-19 pandemic. This condition results in the minimal ability of students to make garnishes. Based on this background, the proposed training for making drink garnishes and tumpeng were really needed by these students. The methods used in training for making drink garnishes and tumpeng are interactive lectures, practices, questions and answers, and discussions. Training in making drink garnishes and tumpeng were given to class XII in Culinary Service Department at State Vocational High School 1 Sayung. This training begins with filling in the participant attendance list, then opening the activity, providing materials, assistance with the practice of making garnishes, followed by discussion, then ends with a group photo. The level of success of this training can be concluded through 2 (two) indicators, which are the students' enthusiasm for participating in this activity and the students' ability to independently make drink garnishes and tumpeng. The final result obtained was that the students were very enthusiastic about participating in the training from beginning until the end, then the students showed an attitude of having implemented the garnish making process well